Circular RNA DOCK1 promotes bladder carcinoma progression via modulating circDOCK1/hsa‐miR‐132‐3p/Sox5 signalling pathway. (14th April 2019) - Liu, Peihua; Li, Xiaozhou; Guo, Xi; Chen, Jinbo; Li, Chao; Chen, Minfeng; Liu, Longfei; Zhang, Xiangyang; Zu, Xiongbing
Abstract: Objectives: To reveal the role of circular RNA (circRNA) DOCK1 (circDOCK1) as a potential biomarker and therapeutic target and its competing endogenous RNA mechanism in bladder carcinoma (BC). Methods: The next‐generation sequencing (NGS) technology was introduced to screen the circRNA expression profiles of BC using microarray. qPCR and Western blots assay were employed to measure the gene expression in different groups. Cell counting kit‐8, EdU and transwell assays were applied to detect the cell viability, proliferation and migration potential, respectively. Luciferase reporter assay was used to test the binds between hsa‐miR‐132‐3p/Sox5. Xenografted tumour growth of nude mice was performed to test the role of circDOCK1 in vivo. Results: CircDOCK1 was upregulated in BC tissues and cell lines. Repression of circDOCK1 reduced cell viability, inhibited cell proliferation and curbed the cell migration potential of BC cell. CircDOCK1 played its role via regulation of circDOCK1/hsa‐miR‐132‐3p/Sox5 pathway in BC cells. Suppression circDOCK1 inhibited the tumour growth in vivo. Conclusion: In this study, we revealed that circDOCK1 affected the progression of BC via modulation of circDOCK1/hsa‐miR‐132‐3p/Sox5 pathway both in vitro and in vivo and providing a potential biomarker and therapeutic targets for BC.